Youtube As Innovation in Teaching Words Equivalent of Bahasa Indonesia - Wirahyuni, K (KnE Social Sciences, 2019)
Language establishment and development is one of the subjects in Bahasa Indonesia Department which more focus on the application or use of Bahasa Indonesia in the society and the development of Bahasa Indonesia in accordance with the progress of the times. One of them is to allow foreign words into the word equivalent in Bahasa Indonesia. There are still few people who know or even use the words equivalent in daily life. In fact, the words equivalent of Bahasa Indonesia are no less cool than the foreign language. In today’s technological age, audiovisual information gets more attention in society, especially for today’s teenagers. They seem addicted in watching videos rather than reading books. All of information and lesson which are gained from watching video is more quickly absorbed than giving lecture or displaying material in the slides. Therefore, a short video of word equivalent is made and it is broadcasted on Youtube. This kind of innovation also takes advantage from media such as gadget or portable computers in learning. Teaching words equivalent through Youtube media are done into three steps, namely: introduction of words equivalent, creating video of words equivalent, and implicating video of words equivalent on Youtube. This research is a descriptive qualitative research. Around 96% of college students deliver positive responses on the video which is made and displayed properly as learning material about word equivalent. All college students state that Youtube can improve their learning motivation. Youtube can also add their creativity to create an interesting video. Teachers can take advantage of short video about word equivalent on Youtube and apply it into learning material, such as making or organizing sentences, writing paragraphs, writing poems, delivering speech, and so on. The more often word equivalent are applied or used by students, the vocabulary of Bahasa Indonesia also automatically increase. Innovation of teaching word equivalent of Bahasa Indonesia into a short video on Youtube is a creative learning which is adapted on the current development. Keywords: Youtube, learning innovation, words equivalent of Bahasa Indonesia